A Comparison of High-Dose Cytarabine During Induction Versus Consolidation Therapy in Newly Diagnosed AML. Issue 6 (December 2018) - Schwarer, Anthony P.; Butler, Jason; Jackson, Kathryn; Beligaswatte, Ashanka; Martin, Louisa; Kennedy, Glen; Daniela, Zantomio; Lewis, Ian; Hiwase, Devendra; Wight, Joel; He, Simon; Grigg, Andrew; et al.
Abstract : Abstract: The proportion of patients with acute myeloid leukemia (AML) cured is increased by administering high-dose cytarabine (HiDAC). It remains uncertain whether to administer HiDAC as induction or consolidation, and whether ≥1 cycle of HiDAC is required. Our retrospective study of 416 adult AML patients, excluding good risk cytogenetics, compared a single cycle of HiDAC-based therapy followed by 2 cycles of standard-dose cytarabine (SDAC) (HiDAC induction cohort) with SDAC-based chemotherapy followed by 2 cycles of HiDAC-based chemotherapy (HiDAC consolidation cohort). Complete remission (CR) rate was greater in the HiDAC induction cohort (90% vs 78%, P  < 0.01) which did not lead to an improved overall survival (48% vs 43%, P  = 0.18) or disease-free survival (DFS) (39% vs 45%, P  = 0.95). We noted that, after censoring for allogeneic hematopoetic stem cell transplant (alloHSCT) in CR1, the cumulative incidence of relapse was lower in the HiDAC consolidation cohort in patients with intermediate risk cytogenetics (68% vs 44%, P  = 0.01), which lead to a greater DFS (30% vs 47%, P  = 0.095). In the patients with adverse risk cytogenetics, the RR was numerically greater in the HiDAC consolidation cohort (52% vs 80%, P  = 0.60) which lead to a lower DFS (27% vs 4%, P  = 0.11). Our data show that, although the HiDAC induction cohort (1 cycle of HiDAC) achieved a greater CR rate, there were no overall survival differences between the 2 cohorts, and that the HiDAC consolidation cohort (2 cycles of HiDAC) had a lower RR and greater DFS in those patients with intermediate risk cytogenetics who did not undergo alloHSCT in CR1.